Developing integrated care: Treating foot wounds in people with diabetes mellitus exposed by Covid-19 - Sri Lestari Dwi Astuti; Suyanto Suyanto (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Diabetes mellitus is a chronic disease that affects many people around the world. WHO predicts the prevalence in 2030 will increase to 61 percent and it is estimated that 70 percent will become a pandemic in developing countries including Indonesia. Various complications require long-term care and require regular monitoring. One of the complications that is often experienced is diabetic foot ulcers which have increased in cases during the Covid-19 pandemic so that they require optimal service.Purpose: Developing a nursing service model for type 2 diabetes mellitus (DM) patients, especially the treatment of diabetic foot wounds associated with the covid-19 pandemic.Method: Research design using quasi-experiment with a plan pre and post-test without control group design, namely comparing the condition of the wound, the effectiveness of the length of time for healing based on the frequency of wound care between 26 respondents who were exposed to covid-19 and 34 respondents who were not exposed. Data analysis used the chi-square test.Results: There is a difference in healing based on the frequency of treating diabetic foot wounds between those exposed to covid-19 and not exposed to obtain a p-value of 0.013 <0.05. There is a difference in healing based on the frequency of treating diabetic foot wounds in patients exposed to covid-19 between those who have arterial injuries and those who do not have arterial injuries, obtaining a p-value of 0.049 <0.05. Then there are differences in the condition of leg injuries before and after being treated in patients who are not exposed to covid-19, obtaining a p-value of 0.00 <0.05. Whereas in patients exposed to covid-19, there was no difference with a p-value of 0.160 > 0.05.Conclusion: All hypotheses proposed except for the hypothesis that there is a difference in the condition of the wound between those exposed to covid-19 and those who were not exposed before and after being given treatment.Suggestion: In providing wound care to diabetic patients, it should be started by reviewing their history of having been exposed to covid-19. Furthermore, an assessment is made of whether the patient has an arterial wound so that the wound care that will be given is more appropriate and effective.